2005
DOI: 10.1002/adfm.200305155
|View full text |Cite
|
Sign up to set email alerts
|

Ag‐Functionalized Carbon Molecular‐Sieve Membranes Based on Polyelectrolyte/Polyimide Blend Precursors

Abstract: We prepared dense flat‐sheet Ag‐functionalized carbon molecular‐sieve (CMS) membranes from blends of P84 co‐polyimide and a sulfonated poly(ether ether ketone) with a Ag+ counterion (AgSPEEK). These blends offer the possibility of producing new functionalized precursor structures, which were previously not possible, such as integrally skinned asymmetric hollow fibers. Membranes prepared at a pyrolysis end temperature of 800 °C showed a maximum permeability for all tested gases at a Ag content of approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…CMSMs are usually prepared by carbonization of polymeric precursors such as polyimide [10,141,142], polyacrylonitile (PAN) [29], poly(phthalazinone ether sulfone ketone) [163], poly(phenylene oxide) [91,161], and cellulose derivatives [65,68,72,73,90,99]. CMSMs present high mechanical strength and moderate modulus due to their graphitic or turbostratic structure compared to graphitized fibers [130].…”
Section: Carbon Molecular Sieve Membranesmentioning
confidence: 99%
“…CMSMs are usually prepared by carbonization of polymeric precursors such as polyimide [10,141,142], polyacrylonitile (PAN) [29], poly(phthalazinone ether sulfone ketone) [163], poly(phenylene oxide) [91,161], and cellulose derivatives [65,68,72,73,90,99]. CMSMs present high mechanical strength and moderate modulus due to their graphitic or turbostratic structure compared to graphitized fibers [130].…”
Section: Carbon Molecular Sieve Membranesmentioning
confidence: 99%
“…Incorporating inorganic nanoparticles into the carbon matrix to fabricate hybrid CMS membranes is considered an effective route to tune the disordered pore structure of pure CMS membranes and improve gas permeation via reducing the gas diffusion through the CMS membrane. Research has reported that hybridizing nanoparticles, such as metal clusters [40,41,42,43,44], metal oxides [44,45,46,47], inorganic particles [48,49,50,51], and porous materials [52,53,54,55,56,57,58,59], into the carbon matrix obviously enhances the gas permeability or selectivity of derived carbon membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Although CMSMs are still in the developmental phase, these membranes are believed to be promising candidates for gas separation and membrane reactors because: (i) they are relatively easy to manufacture; (ii) they have low production and raw material costs; (iii) they offer the molecular sieve dispersed Ag nanoparticles into P84 and SPEEK precursors [47,48] and achieved higher O 2 /N 2 selectivity values; the increase in gas-pair selectivity observed was attributed to the selective diffusion pathways that occur along the silver nanoparticles' surface. Xiao et al [49] reported the preparation of c-CMSMs from Ag + SPAEK; they observed that the silver doped CMSMs exhibited higher CO 2 /CH 4 selectivities (it was attributed to the greater interconnection among the ultramicropores formed by the migration of silver) and permeabilities.…”
Section: Introductionmentioning
confidence: 99%